The determinants of capital structure of real estate firm in Malaysia / Nur Syazana Lina Kamal - Kamal, Nur Syazana Lina (2015)
The purpose of this study is to investigate the determinants of capital structure of real estate firm in Malaysia. The determinants that been investigate is profit, growth opportunities, asset tangibility and size. The data is in Malaysia data and the data is from 2010 until 2014. The data will be test using skewness and kurtosis, hausman test, breucsh and pagan lm test, linear regression analysis (OLS regression) , and variance inflation factor test (VIF). The findings of this result show that the profit has negative relationship with the leverage. It show that higher profitability firm will use external fund for leverage. For the growth opportunities, the findings shows that the high growth firm will issue more equity and have less debt. Findings on asset tangibility show that negative relationship with leverage. For size, the result show that firm that expand will likely to use more leverage.